Trawl locations of walleye pollock and Atka mackerel fisheries in the Bering Sea, Aleutian Islands and Gulf of Alaska from 1977-92 - Fritz, Lowell W; Alaska Fisheries Science Center (U.S.) (Seattle, WA : National Marine Fisheries Service, Alaska Fisheries Science Center, 1993)
Mode of access: Internet.